The Oral Status of Adult Population in the Croatian Town of Knin: a Cross Sectional Study - Robert Marić; Ana MALČIĆ IVANIŠEVIĆ; Jurica Matijević; Silvana JUKIĆ KRMEK (University of Zagreb. School of Dental Medicine, 2015)
The aim: Epidemiologic studies in many countries show uneven distribution of oral diseases (primarily caries) within the population. This is why more studies are oriented towards specific regions or subpopulations instead of large scale national surveys. The major purpose of this cross sectional study was to obtain relevant data about the oral status of the population of Knin and its surroundings according to the WHO criteria. Subjects and methods: The study included 414 participants aged between 18 and 65. The recorded variables included general anamnestic data, extraoral status, oral mucosa status, temporomandibular joint status, dental, periodontal and prosthetic status, and the need for dental restoration. The comparison between different groups regarding age, gender, educational level and origin was made. Results: DMFT index was 17.3 - with on average 1.7 caries, 6.2 fillings, and 9.4 teeth extracted. SiC index equaled 26.4. The difference was significant regarding the level of education and age (p<0.001). The percentages of individuals with the highest CPI scores from 0-4 were 27.3, 16.9, 36.5, 16.4 and 2.9%, respectively. The difference between the age groups in CPI scores was statistically significant, while the differences according to the gender and origin were not significant (p=0.001). Conclusion: The population of Knin and the surrounding area exhibited very bad oral status which can be attributed to the consequences of the war in the 1990-ies, the economic transition, and the lack of national program for oral health promotion.